The Effect Of Capital Intensity, Institusional Ownership, And Firm Size On Tax Avoidance - bramantyo, revy; Atmini, Sari (Telaah Ilmiah Akuntansi dan Perpajakan, 2026)
This study examines the effect of capital intensity, institutional ownership, and firm size on tax avoidance. This research focuses on non-cyclical consumer sector companies because this sector has distinctive characteristics compared to other sectors. Companies in this sector provide essential goods that remain in demand even during economic downturns, including the COVID-19 pandemic period. Therefore, the sector offers a relevant context for examining tax avoidance, as firms may simultaneously face pressure to maintain profitability, liquidity, and tax compliance. The sample consists of non-cyclical consumer sector companies listed on the Indonesian Stock Exchange (IDX) during the 2020–2022 period. Using a purposive sampling technique, 33 firms were selected, resulting in 99 firm-year observations. Tax avoidance is measured by the Effective Tax Rate (ETR), and hypothesis testing is conducted using multiple linear regression. The results show that (1) capital intensity has no significant effect on tax avoidance, (2) institutional ownership has a negative effect on tax avoidance, and (3) firm size has a positive effect on tax avoidance. These findings contribute to the tax avoidance literature by providing evidence from a resilient and essential sector during the pandemic and post-pandemic recovery period.